กระบวนการผลิต การนำเสนอ และการสร้างความหมายเชิงสัญญะในรายการเดอะวอยซ์ไทยแลนด์ - กะรัตพลอย ถ้ำแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This qualitative research aims to study the production, presentation and signification of the licensed reality TV program, entitled "The Voice Thailand", and to analyze the internal and external media organization’s factors which affect its text and presentation. The Television production, Television presentation, Semiology, Reality game show and the Model of media organization in a field of social forces through glocalization concepts are applied along with textual analysis and in-depth interview methodology as research tools. The finding about its production shows that the program is partially-scripted and recorded through multi cameras system, which allows the contents to be changed and shaped by editing in the postproduction process. The program is controlled by the license’s owner in all production processes. The presentation of the program consists of 2 main presentation forms, which are On-stage form and VTRs form. The analyzing on program’s signification finds that there are 4 main groups of connotative meaning constructed as follow; 1) the meaning of "singer" 2) the meaning of "contest" 3) the meaning of "The Voice" as the distinctive program and "Coach" 4) other special meanings, which are all constructed via the different combination of signs. The internal media organization’s factors which affect the program are 1) program’s license ownership 2) local production team 3) coach and contestant, while the external media organization’s factors are 1) audience 2) social and political situation 3) music license 4) sponsorship